The trans-Golgi SNARE syntaxin 10 is required for optimal development of Chlamydia trachomatis - Lucas, Andrea L.; Ouellette, Scot P.; Kabeiseman, Emily J.; Cichos, Kyle H.; Rucks, Elizabeth A. (Frontiers in Cellular and Infection Microbiology, 2015)
Chlamydia trachomatis, an obligate intracellular pathogen, grows inside of a vacuole, termed the inclusion. Within the inclusion, the organisms differentiate from the infectious elementary body (EB) into the reticulate body (RB). The RB communicates with the host cell through the inclusion membrane to obtain the nutrients necessary to divide, thus expanding the chlamydial population. At late time points within the developmental cycle, the RBs respond to unknown molecular signals to redifferentiate into infectious EBs to perpetuate the infection cycle. One strategy for Chlamydia to obtain necessary nutrients and metabolites from the host is to intercept host vesicular trafficking pathways. In this study we demonstrate that a trans-Golgi soluble N-ethylmaleimide–sensitive factor attachment protein (SNARE), syntaxin 10, and/or syntaxin 10-associated Golgi elements colocalize with the chlamydial inclusion. We hypothesized that Chlamydia utilizes the molecular machinery of syntaxin 10 at the inclusion membrane to intercept specific vesicular trafficking pathways in order to create and maintain an optimal intra-inclusion environment. To test this hypothesis, we used siRNA knockdown of syntaxin 10 to examine the impact of the loss of syntaxin 10 on chlamydial growth and development. Our results demonstrate that loss of syntaxin 10 leads to defects in normal chlamydial maturation including: variable inclusion size with fewer chlamydial organisms per inclusion, fewer infectious progeny, and delayed or halted RB-EB differentiation. These defects in chlamydial development correlate with an overabundance of NBD-lipid retained by inclusions cultured in syntaxin 10 knockdown cells. Overall, loss of syntaxin 10 at the inclusion membrane negatively affects Chlamydia. Understanding host machinery involved in maintaining an optimal inclusion environment to support chlamydial growth and development is critical toward understanding the molecular signals involved in successful progression through the chlamydial developmental cycle.